Emotional intelligence, alexithymia, stress, and people's reasons for listening to music. (September 2019) - Lonsdale, Adam J.
The present study investigated the relationship between people's reasons for listening to music, trait emotional intelligence, and alexithymia whilst also controlling for the effect of participants' gender, age, and perceived stress levels. In keeping with previous research, initial findings indicated that emotionally intelligent individuals were less likely to use music to relieve and alleviate negative moods, whilst those who had high scores on a measure of alexithymia were more likely to use music for the same reasons. However, when the effects of gender, age, and perceived stress were controlled for, these relationships were no longer significant and previously non-significant relationships between trait emotional intelligence and using music to manipulate arousal and to reminisce about the past were found to be significant. Together these findings suggest that emotional intelligence is related to the reasons why people listen to music but not in the way that previous research had suggested, and the apparent links between emotional intelligence and mood management might be better explained by the stress experienced by participants at the time of questioning.